Customs institutions development strategy: design and implementation issues - V. V. Makrusev (Вестник университета)
Today, quality requirements for customs administration are increasing, but customs technology is not sufficiently productive: with the accumulated experience of solving management tasks, there is no modern, unified methodological support for strategic planning in this area. There is an urgent need to develop and implement a new concept, strategy or development programme for the Federal Customs Service of the Russian Federation in the context of quantitative and expert forecasts for the long term. The aim of the study was to analyse the existing approaches and methodological support used to research and develop strategic planning documents on national (economic) security of the Russian Federation, and to substantiate proposals and approaches to the design of strategies and programmes for the development of public administration and administration institutions in terms of foreign economic and customs activities. The methodological basis of the study was a comparative analysis of Russian and foreign experience in addressing development challenges in the customs sphere. On the basis of the generalised experience of theoretical approaches, recommendations and practices of strategic planning documents development the qualitative expertise of the structure of key normative-legal documents, on the basis of which the customs authorities carry out their activities, has been carried out. The problem areas of the process of design and modernization of the structure of documents in the field of customs administration are identified and recommendations for their adjustment are presented. It is proposed to apply intelligent systems of computer-aided designing and to transit from model of static designing of customs institutions to model of operative controlling of spheres of foreign economic and customs activity and dynamic (continuous) designing of customs systems on principles of self-organisation and self-development.